Low-dose M.tb infection but not BCG or MTBVAC vaccination enhances heterologous antibody titres in non-human primates - Peralta Alvarez, Marco Polo; Jones, Holly; Redondo Azema, Hugo; Davis, Chloe; White, Andrew D.; Sarfas, Charlotte; Dennis, Mike; Li, Shuailin; Wright, Daniel; Puentes, Eugenia; Kimuda, Simon; Belij-Rammerstorfer, Sandra; et al. (Frontiers in Immunology, 2024)
Mycobacteria are known to exert a range of heterologous effects on the immune system. The mycobacteria-based Freund’s Complete Adjuvant is a potent non-specific stimulator of the immune response used in immunization protocols promoting antibody production, and Mycobacterium bovis Bacille Calmette Guérin (BCG) vaccination has been linked with decreased morbidity and mortality beyond the specific protection it provides against tuberculosis (TB) in some populations and age groups. The role of heterologous antibodies in this phenomenon, if any, remains unclear and under-studied. We therefore set out to evaluate antibody responses to a range of unrelated pathogens following infection with Mycobacterium tuberculosis (M.tb) and vaccination with BCG or a candidate TB vaccine, MTBVAC, in non-human primates. We demonstrate the significant increase in the titer of antibodies against SARS-CoV-2, cytomegalovirus, Epstein-Barr virus, tetanus toxoid, and respiratory syncytial virus antigens following infection with M.tb after low-dose aerosol infection. The magnitude of some of these responses correlated with TB disease severity. However, vaccination with BCG administered by the intradermal, intravenous or aerosol routes, or intradermal delivery of MTBVAC, did not increase antibody responses against unrelated pathogens. It is therefore unlikely that heterologous antibodies contribute to the non-specific effects of these vaccines. The apparent dysregulation of B cell responses associated with TB disease warrants further investigation, with potential implications for risk of B cell cancers and novel therapeutic strategies.